214k views
19 votes
Solve the System of Equations -4x + 9y = 14 12x - 10y = - 8

User Akkie
by
5.3k points

2 Answers

3 votes

Explanation:

HERE,

two equation are,

●-4x+9y=14••••••••••••(equation I)

●12x-10y=-8•••••••••••(equation II)

First multiplying 3 in equation I

we get,


\bold{3×(-4x+9y=14) }

=
\bold{ -12x+27y=42 }••(equation III)

Then,

we combine the equationii and equation III.

we get that,


\bold{12x-10y-12x+27y=-8+42 }


\bold{\cancel{12x}-10y\cancel{-12x}+27y=-8+42 }


\rightsquigarrow
\bold{17y=34 }


\rightsquigarrow
\bold{ y=(34)/(17) }


\rightsquigarrow
\boxed{ y=2 }

Then,

put the value of y in equation II.

WE get,


\rightsquigarrow
\bold{12x-10×2=-8 }


\rightsquigarrow
\bold{ 12x-20=-8 }


\rightsquigarrow
\bold{ 12x=-8+20 }


\rightsquigarrow
\bold{ 12x=12 }


\rightsquigarrow
\bold{ x=(12)/(12) }


\rightsquigarrow
\boxed{ x=1 }

So,

solution of the two equation (-4x+9y) and (12x-10y=-8) is (1,2)

User TheBeardedBerry
by
5.2k points
9 votes

Answer:

(1, 2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtract Property of Equality

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

-4x + 9y = 14

12x - 10y = -8

Step 2: Rewrite Systems

-4x + 9y = 14

  1. Multiply everything by 3: -12x + 27y = 42

Step 3: Redefine Systems

-12x + 27y = 42

12x - 10y = -8

Step 4: Solve for y

Elimination

  1. Combine 2 equations: 17y = 34
  2. Divide 26 on both sides: y = 2

Step 5: Solve for x

  1. Define equation: 12x - 10y = -8
  2. Substitute in y: 12x - 10(2) = -8
  3. Multiply: 12x - 20 = -8
  4. Isolate x term: 12x = 12
  5. Isolate x: x = 1
User JKhuang
by
5.7k points